The phenomenon of the adverse market reaction to dividend change announcements : New evidence from Europe - Elisabete Simões, Vieira (2007)
The dividend policy is one of the most debated topics in the finance literature. According to the dividend signalling hypothesis, which has motivated a significant amount of theoretical and empirical research, dividend change announcements trigger share returns because they convey information about management’s assessment on firms’ future prospects. Consequently, a dividend increase (decrease) should be followed by an improvement (reduction) in a firm’s value. Although there are empirical evidence supporting the positive relationship between dividend change announcements and the subsequent share price reactions, some studies have not supported this idea. Furthermore, several studies found evidence of a significant percentage of cases where share prices reactions are opposite to the dividend changes direction, like the works of Asquith and Mullins (1983), Benesh, Keown and Pinkerton (1984), Born, Mozer and Officer (1988), Dhillon and Johnson (1994) Healy, Hathorn and Kirch (1997), and, more recently, Vieira (2005). We introduce a new approach to investigate the relationship between the market reaction to dividend changes and future earnings changes with the purpose of understanding why the market sometimes reacts negatively (positively) to dividend increases (decreases). We find only weak evidence for the dividend information content hypothesis. The Portuguese results suggest that the adverse market reaction to dividendchange announcements is basically due to the fact that the market does not understand the signal given by firms though dividend change announcements. Moreover, we find no evidence of the inverse signalling effect, except for the UK market. The results suggest that the UK market investors have more capability to predict future earnings than the investors of the Portuguese and the French markets